Analysis on 5G XR and enhancement on media service - Xiaonan SHI; Chunshan XIONG; Hui NI; Dan WANG (Dianxin kexue)
5G XR and enhancement on media service are very important business scenarios in 5G-Advanced network.With the increasing user demands for emerging new media services, 5G network needs to make corresponding enhancements for media services such as XR.The main business scenarios of XR and augmented multimedia were mainly introduced, including immersive virtual reality, augmented reality, remote control technology based on mixed reality, virtual factory, remote unmanned aerial vehicle control, etc.For the typical business scenarios of XR, there were already some specifications and on-going studies in 3GPP.Based on these existing activities, 5G network need further enhancements including 5G QoS framework for XR service, coordination between network and application, synchronization of flows of multi-user and multi-stream, power saving of terminals and network etc., so that the 5G network could provide better support to 5G XR and enhanced media services leveraging the above enablers.